2012
DOI: 10.1016/j.marpol.2011.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives for implementing fisheries certification in developing countries

Abstract: This paper discusses the future of the Marine Stewardship Council (MSC), a marketbased certification program, in developing countries and exposes the challenges and opportunities for fish producers. The MSC needs to attract the interest of more fishing enterprises from these regions to increase its global presence. Because most fisheries in developing countries cannot meet the MSC standards, or afford the certification process costs, we suggest that there is a need for developing different levels within the MS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(39 citation statements)
references
References 23 publications
2
34
0
3
Order By: Relevance
“…Currently, the Marine Stewardship Council (MSC) label is the most widespread worldwide, with 220 certified fisheries accounting for about 10% of the global catch, and it has a large presence in the marketplace of developed countries [4]. Retailers, such as Sainsbury's, Tesco, Marks and Spencer, Wal-Mart and Whole Foods Market, are selling MSC-labeled products [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, the Marine Stewardship Council (MSC) label is the most widespread worldwide, with 220 certified fisheries accounting for about 10% of the global catch, and it has a large presence in the marketplace of developed countries [4]. Retailers, such as Sainsbury's, Tesco, Marks and Spencer, Wal-Mart and Whole Foods Market, are selling MSC-labeled products [5].…”
Section: Introductionmentioning
confidence: 99%
“…Having originated in developed countries, consumer studies of seafood eco-labeling have shown little engagement with developing countries, where few fisheries have been awarded an eco-label [5]. The studies addressing consumers' willingness-to-pay (WTP) for eco-labeled seafood often are based on contingent valuation survey data.…”
Section: Introductionmentioning
confidence: 99%
“…Described by interviewees in the greatest detail and considered more often than the other categories, large consolidated companies with good informational support may be more likely to support third party certification. Large size facilitates certification due to reduced transaction costs associated with economies of scale [14,17,18], and their visibility and public presence expose them to more pressure from advocacy groups [14,19,20]. Companies that were highly selective of their target species were also more successful at certification [1].…”
Section: Analytical Frameworkmentioning
confidence: 99%
“…While both certification systems are global in scope, the great majority of certified fisheries are concentrated in the developed world (less so for the FOS) (Pérez-Ramírez et al 2012;Ponte 2012). In response to criticisms of its developed-world bias, the MSC created the ''Developing World Program,'' which provides financial and technical assistance to artisanal fisheries in the developing world and is increasing its involvement in these fisheries (Dias and Viguié 2013).…”
Section: Formalization Of Trade and Certificationmentioning
confidence: 99%
“…Several authors, questioning the potential of private-sector certification to influence large national fisheries, argue that where fisheries governance is precarious, certification will simply create a class of elite fisheries that qualify for certification while most local fisheries are left to their own devices (Kaiser and Edward-Jones 2006;Pérez-Ramírez et al 2012). Tlusty (2012) analyzes the impact of certification on salmon aquaculture farming.…”
Section: G Mcgrath Et Almentioning
confidence: 99%